THE INFLUENCE OF FINANCIAL RATIOS, COMPANY SIZE AND INFLATION ON FIRM VALUE IN INFRASTRUCTURE COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE IN 2019-2023 - Farhan Adin Saputra; Enggar Diah Puspa Arum; Salman Jumaili (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to examine whether financial ratios, company size, and inflation affect the value of a company. The financial ratios used in this study include liquidity, profitability, and solvency ratios. The approach used in this study is a quantitative approach. The population used in this study consists of infrastructure sector companies listed on the Indonesia Stock Exchange from 2019 to 2023. The sample determination in the study uses a purposive sampling method, resulting in 57 companies with a total of 5 years of observations, so the total sample in this study is 285 companies. The data analysis method in this study uses multiple linear regression with SPSS (Statistical Package for Social Science) software version 29. The results of this study indicate that liquidity, profitability, solvency, inflation, and company size ratios simultaneously affect the value of a company. Partially, profitability, solvency, and company size affect the value of a company, while liquidity and inflation do not affect the value of a company.